Criterion of unitary similarity of minimal passive scattering systems with a given transfer function - Arov, D. Z.; Nudel'man, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish necessary and sufficient conditions under which all minimal passive scattering systems that have a given transfer operator function are unitarily equivalent. These conditions can be significantly simplified in special cases important for applications, in particular, in the case where a transfer function is rational and in a more general case where this function is pseudoextendable.